Market conditions of international VET providers: a comparative analysis of Australia, UK, USA, and Germany - Peters, Susanne [Verfasser] (My University, 2021)
“VET (vocational education and training) is a highly complex, multidimensional worldwide phenomenon with diverse structures. Additionally, very different actors define the functions of a national (or even a regional) VET system. The paper contributes to a better understanding of the policy frameworks and current states of such systems. Therefore, we focus on selected VET systems in order to understand their specifics and thus, their market conditions. A qualitative approach is used to answer the research question regarding which conditions create or support market-based opportunities for the provision of commercial vocational training services. We find that the liberalism and deregulation of the VET sectors, as well as the marketisation of VET practices, lead to incentives to internationalise VET offers. Thinking in terms of skills, the kind of education system does not play a role. This is the case in liberal market-driven VET approaches (here, the UK, the USA and Australia) and is mirrored in the micro-analysis categories of curricula, learning location, content, and learning process.” (author’s abstract; BIBB-Doku)
Keywords: S System beruflicher Bildung; 370; 330; Berufsbildung; Berufsbildungssystem; Bildungsmarkt; Anbieter; Internationaler Vergleich; Vereinigtes Königreich; USA; Bundesrepublik Deutschland; Australien